PENGARUH GAYA HIDUP DAN FASILTAS TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI CAFÉ YOU FEE MEDAN - Sigalingging, Nursima; Hutagalung, Maria; Eva Solita Pasaribu (JURNAL MUTIARA MANAJEMEN, 2024)
The of purpose study is to ascertain how amenities and lifestyle affect customers' decisions to buy from Cafe You Fee Medan. Ninety-four Cafe You Fee Medan patrons made up the sample and research. Purposive sampling is the sampling strategy employed, and multiple linear regression analysis is the data analysis approach.Finding out how facilities and lifestyle impact customers' decisions to purchase from Cafe You Fee Medan is the aim of this study. Ninety-four customers of Cafe You Fee Medan comprised and the sampling strategy used is purposefulsampling. According to the study's findings, the lifestyle variable (X1) significantly and favorably influences the purchasing choice variable (Y), and the facility variable (X2) also significantly and favorably influences the purchasing decision variable. It can be concluded that the influence of each variable is seen at the same time, that the value of Fcount (489.502) is greater than Ftable (3.10) or sig. is 0.000 < 0.05. Lifestyle and facility variables account for 91.5% of purchasing decisions